No impact of biocontrol agent’s predation cues on development time or size of surviving Aedes al-bopictus under optimal nutritional availability - Russell,M; Cator,L (Insects, 2022)
Cyclopoid copepods have been applied successfully to limit populations of highly invasive Aedes albopictus mosquitoes that can transmit diseases of public health importance. However, there is concern that changes in certain mosquito traits, induced by exposure to copepod predation, might increase the risk of disease transmission. In this study, third instar Ae. albopictus larvae (focal individuals) were exposed to Megacyclops viridis predator cues associated with both the consumption of newly hatched mosquito larvae and attacks on focal individuals. The number of newly hatched larvae surrounding each focal larva was held constant to control for density effects on size, and the focal individual’s day of pupation and wing length were recorded for each replicate. Exposing late instar Ae. albopictus to predation decreased their chances of surviving to adulthood, and three focal larvae that died in the predator treatment showed signs of melanisation, indicative of wounding. Among surviving focal Ae. albopictus, no significant difference in either pupation day or wing length was observed due to copepod predation. The absence of significant sublethal impacts from M. viridis copepod predation on surviving later stage larvae in this analysis supports the use of M. viridis as a biocontrol agent against Ae. albopictus.